(untitled) (Interdisciplinary Studies Journal, 2024)
Influenza is a seasonal and viral disease that affects the respiratory system and can cause serious damage and deaths in risk groups, in which the elderly are included. Through annual campaigns, public vaccination policy aims to reduce morbidity and mortality from this disease through high and homogeneous vaccination coverage in priority groups. The present study aimed to analyze influenza vaccination coverage in elderly people in the Western Region of the State of Mato Grosso. This was a retrospective and analytical time series study, based on vaccination coverage of annual campaigns against Influenza from 2018 to 2023, considering the 12 municipalities in the Western Region of the State of Mato Grosso. Data collection on vaccination coverage was carried out through the database of the Information Technology Department of the Unified Health System (DATASUS), linked to the Information System of the National Immunization Program (SI-PNI). It is essential that vaccination actions are carried out in the best way possible, and achieve the common objective of offering protection to the health of the population as a whole, as maintaining high vaccination coverage can prevent the impact of influenza from being even greater. in morbidity and mortality in the elderly.